Validating The Problem-Based Learning Module Based on Local Wisdom Material to Improve Elementary School Students' Critical Thinking Skills in Natural and Social Science Education (IPAS) - Uslan; Ummu Aiman; Minsih (Postgraduate, University of Mataram, 2025)
The current research aims to validate a problem-based module based on local wisdom material to influence elementary school students' critical thinking skills. A mixed-method research design with quantitative descriptive analysis was used to explore the experts' validation, and observation was conducted to prove the influence of the module for students' critical thinking skills. The participants were two experts who were purposely selected to measure the module's appropriateness and ten students who were conveniently selected to prove the influence of the module on students critical thinking skill. The experts' validation considered several aspects, such as the accordance of the module to the syllabus, the overall appropriateness of the module, and the media acceptance of the module. Based on the module's accordance with the syllabus, the overall expert rating was 4.71, the pedagogical aspect of the module acceptance was 4.66, and the media characteristic of the module was 4.50, indicating the agreement of the experts on the appropriateness of the module. In terms of the impact of the module on students' critical thinking skills, observation was conducted measuring the students' ability in critical thinking throughout the learning process with the module. It was found most of the students were able to conceptualize a question, analyze arguments, clarify and answer questions, do observation and do evaluation based on the observation, make deductions and draw conclusions and evaluate the outcomes, and formulate inductions and evaluate them.